Acute Effect of Enhanced External Counterpulsation on the Carotid Hemodynamic Parameters in Patients With High Cardiovascular Risk Factors - Zhang, Yahui; Mai, Zhouming; Du, Jianhang; Zhou, Wenjuan; Wei, Wenbin; Wang, Hui; Yao, Chun; Zhang, Xinxia; Huang, Hui; Wu, Guifu (Frontiers in Physiology, 2021)
Purpose Enhanced external counterpulsation (EECP) can improve carotid circulation in patients with coronary artery disease. However, the response of carotid hemodynamic parameters induced by EECP in patients with high cardiovascular risk factors remains to be clarified. This study aimed to investigate the acute effect of EECP on the hemodynamic parameters in the carotid arteries before, during, and immediately after EECP in patients with hypertension, hyperlipidemia, and type 2 diabetes. Methods Eighty-three subjects were recruited into this study to receive 45-min EECP, including patients with simple hypertension (n = 21), hyperlipidemia (n = 23), type 2 diabetes (n = 18), and healthy subjects (n = 21). Hemodynamic parameters in both common carotid arteries (CCAs) were measured and calculated from Doppler ultrasound images. Peak systolic velocity (PSV), end-diastolic velocity (EDV), mean inner diameter (ID), systolic/diastolic flow velocity ratio (VS/VD), flow rate (FR), and resistance index (RI) were monitored before, during, and immediately after 45-min EECP. Results EDV and VS/VD were significantly reduced, while RI of CCAs was significantly increased among four groups during EECP (all P < 0.01). Additionally, the ID of CCAs and the FR of left CCA increased in patients with hyperlipidemia during EECP (P < 0.05). PSV of left CCA was reduced in patients with type 2 diabetes (P < 0.05). Moreover, immediately after EECP, ID was significantly higher in patients with hyperlipidemia. The RI of patients with hypertension and PSV and VS/VD of patients with type 2 diabetes were significantly lower compared with baseline (all P < 0.05). Conclusion EECP created an acute reduction in EDV, PSV, and VS/VD, and an immediate increase in the RI, FR, and ID of CCAs among the four groups. Additionally, a single 45-min session of EECP produced immediate improvement in the ID of patients with hyperlipidemia, the RI of patients with hypertension, and the PSV and VS/VD of patients with type 2 diabetes. The different hemodynamic responses induced by EECP may provide theoretical guidance for making personalized plans in patients with different cardiovascular risk factors.